1978
DOI: 10.1063/1.436092
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy transfer studies in CO2–hydrocarbon mixtures

Abstract: Rate constants for the transfer of energy from COiOO'I) to ethane and n-butane were measured using the laser induced fluorescence technique. The large magnitudes and the negative temperature dependence of the energy transfer rates indicate that near-resonant energy transfer processes caused by long range forces are responsible for the deactivation of the asymmetric stretching mode of CO 2 , It is shown that the combination bands in the alkanes are likely to receive the energy from CO 2 (OO'I). Using Sharma-Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Transformation of ammonia N (NH 3 -N) to NO 3 -N is favored by soil-water pH values <7.1, and volatilization of N occurs at high pH values; e.g., Rao and Batra (1983) observed that 62% of applied NH 3 -N was lost in 10 days when applied to an alkali soil with a pH of 10.2. With respect to P, Olson and Sander (1988) have shown that a majority of calcareous soils with pHs in the range of 7.5-8.5 are defi cient in P for optimum corn production because at pHs >7, phosphate minerals with extremely low phosphate (PO 4 3-) solubilities form.…”
mentioning
confidence: 99%
“…Transformation of ammonia N (NH 3 -N) to NO 3 -N is favored by soil-water pH values <7.1, and volatilization of N occurs at high pH values; e.g., Rao and Batra (1983) observed that 62% of applied NH 3 -N was lost in 10 days when applied to an alkali soil with a pH of 10.2. With respect to P, Olson and Sander (1988) have shown that a majority of calcareous soils with pHs in the range of 7.5-8.5 are defi cient in P for optimum corn production because at pHs >7, phosphate minerals with extremely low phosphate (PO 4 3-) solubilities form.…”
mentioning
confidence: 99%
“…They make an important comparative pair because they are isoelectronic, have the same mass, and have similar vibrational frequencies. CO 2 has long been used in this role (see, for example, refs [1][2][3][4][5][6][7][8][9][10][11][12], but the studies of N 2 O began much more recently and are far less extensive. [13][14][15][16][17][18][19][20][21][22][23][24][25] Most experimental measurements have been confined to deactivation of both CO 2 and N 2 O excited to the (00 0 1) vibrational level of the asymmetric stretch mode, ν 3 .…”
Section: Introductionmentioning
confidence: 99%